Delocalized Arbitration myth or reality? Analyzing the interplay of the delocalization theory in different legal systems. - Habib, Sadaff (2013)
This dissertation seeks to examine the stigma attached to the idea of a delocalized or floating or transnational arbitration. Whilst the debate on this subject has ensued for decades, this paper seeks to analyze whether the reasons for its slow development in the sphere of international commercial arbitration is due to its characteristics or if it’s acceptability and development is attached to the kind of legal system that operates in a given State. The analysis herein is limited to the jurisdictions of England, USA and France with an overview of the UAE. Data has been gathered mostly from journals on the subject and interviews of well-known multi-jurisdictional practitioners. Interestingly it has been found that delocalization or trans-nationalization is not tied to a particular legal system but is related to the extent to which a state is arbitration friendly. Furthermore, although delocalized arbitration has not been adopted in entirety soft delocalization (with certain aspects of it being adopted) is in play. The implications of this are that as international commercial arbitration continues to expand there may well be a development in the future in the form of an international instrument bridging the ideas of the seat theorists and those of the delocalized protagonists.